Analysis of Mathematics Teachers’ Difficulties in Implementing Differentiated Learning under the Independent Curriculum - Zendrato, Dedy Rahmat; Telaumbanua, Yakin Niat; Mendrofa, Ratna Natalia; Lase, Sadiana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Merdeka Curriculum promotes differentiated learning as a key strategy to address students’ diverse learning needs. However, a preliminary study at SMA Negeri 3 Gunungsitoli indicates that this approach has not been implemented consistently in mathematics classrooms. This study aims to describe how mathematics teachers apply differentiated learning and to analyze the difficulties they face and the factors influencing these difficulties within the Independent Curriculum. This study employed a qualitative descriptive design. Data were collected through interviews, classroom observations, and document analysis involving five mathematics teachers. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings show that teachers have begun to implement differentiation in content, process, and product. However, the implementation remains limited. Major difficulties include time management constraints, diverse student learning characteristics, and challenges in conducting initial diagnostic assessments. Contributing factors include limited facilities, insufficient teacher readiness, and a lack of structured professional training. These findings indicate that differentiated learning in mathematics is still at an early stage of implementation and requires systematic institutional support. This study contributes to the literature by highlighting context-specific challenges faced by mathematics teachers under the Independent Curriculum and provides practical implications for schools and policymakers in designing targeted professional development programs.